A geography of contaminated sites, mental health and wellbeing: The body, home, environment and state at Australian PFAS sites. (August 2022) - Legg, Rupert; Prior, Jason; Adams, Jon; McIntyre, Erica
Abstract: Health geographers have long been interested in the connection between place and mental health, proposing that settings influence mental health and vice versa. Research on environmental contamination has tended to focus on the former part of this relationship, examining how the mental health and wellbeing of residents living nearby are affected by the contamination. There has been little investigation of the latter component: how mental health and wellbeing may shape place. This article seeks to explore how the mental health and wellbeing of residents living on or near environmental contamination may be both affected by and reproduced in place. It considers this in a case study of per- and poly-fluoroalkyl substances (PFAS) contamination in New South Wales, Australia, by drawing on interviews with residents. Focus is placed on examining how residents report psychological distress associated with the contamination and how this distress may permeate beyond the contaminated site to become enmeshed in other places at different scales, such as the body, home, local environment, and state. Ultimately, it is proposed that these places reproduce distress on their own and require just as much attention in addressing adverse psychological effects as the physical contamination itself. Highlights: Residents reported that living near environmental contamination caused psychological distress. This distress was influenced by a resident's relationship to their body, home, local environment and the state. Distress shaped how residents interacted with various places, resulting in changes to their bodies, homes, environment and state. There was the potential these altered places could then compound or amplify residents' distress.